Endothelial dysfunction and immunothrombosis in sepsis - Maneta, Eleni; Aivalioti, Evmorfia; Tual-Chalot, Simon; Emini Veseli, Besa; Gatsiou, Aikaterini; Stamatelopoulos, Kimon; Stellos, Konstantinos (Frontiers in Immunology, 2023)
Sepsis is a life-threatening clinical syndrome characterized by multi-organ dysfunction, caused by a dysregulated or over-reactive host response to infection. During sepsis, the coagulation cascade is triggered by activated cells of the innate immune system, such as neutrophils and monocytes, resulting in clot formation mainly in the microcirculation, a process known as immunothrombosis. Although this process aims to protect the host through inhibition of the pathogen’s dissemination and survival, endothelial dysfunction and microthrombotic complications can rapidly lead to multiple organ dysfunction. The development of treatments targeting endothelial innate immune responses and immunothrombosis could be of great significance for reducing morbidity and mortality in patients with sepsis. Medications modifying cell-specific immune responses or inhibiting platelet-endothelial interaction or platelet activation have been proposed. Herein, we discuss the underlying mechanisms of organ-specific endothelial dysfunction and immunothrombosis in sepsis and its complications, while highlighting the recent advances in the development of new therapeutic approaches aiming at improving short- or long-term prognosis in sepsis.